Integrasi Nilai Etika dalam Supervisi Pendidikan: Kajian Literatur Sistematis - Anggraini, Fitria; Sabila, Ahda; Oktageri, Deris; Akbar, Muhammad; Yuliana, Yuliana; Wakhinuddin, Wakhinuddin (LPPPI Publishing, 2025)
This study aims to analyze the integration of ethical values in educational supervision using the Systematic Literature Review (SLR) approach with the PRISMA method. Based on the analysis of 18 selected articles published between 2018-2024, several studies were found showing that ethical values, such as fairness, responsibility and transparency, play an important role in strengthening the effectiveness of educational supervision. The application of these ethical principles contributes to improving teachers' professional competence, building healthy relationships between supervisors and supervisees and creating an inclusive learning environment. Nonetheless, some challenges were identified, including the lack of clear ethical guidelines, limited training of supervisors and technical barriers in the implementation of technology to support supervision. This study emphasizes the importance of developing ethics-based supervision policies, intensive training and adequate technological infrastructure to support effective supervision. The results of this study provide practical insights for educational practitioners and researchers to strengthen the role of ethics in improving the quality of educational supervision.